Low-temperature-resistant and yellowing-resistant adhesive material as well as preparation method and application thereof

By using a combination of modified ethylene acrylic acid copolymer and polyacrylate pressure-sensitive adhesives, combined with components such as vapor phase silica, antioxidants and organic UV absorbers, existing tape or adhesive materials are solved at low and high temperature conditions. The problem of difficulty in maintaining adhesion and transparency underneath achieves efficient low temperature and yellowing resistance.

CN119391310APending Publication Date: 2025-02-07KUNSHAN YUHUAN PACKAGE MATERIALS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411668225.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing tapes or adhesive materials are difficult to take into account both adhesion and low-temperature yellowing resistance. Especially under ultra-high or ultra-low temperature conditions, adhesion and transparency are difficult to maintain.

Method used

Modified ethylene acrylic acid copolymer is used as the base layer and polyacrylate pressure-sensitive adhesive is used as the adhesive layer. By adding components such as vapor phase silica, antioxidants and organic ultraviolet absorbers, the yellowing resistance of the material is improved. and low temperature resistance.

Benefits of technology

Within a wide temperature range, the material maintains good adhesion and transparency, significantly improving its low temperature and yellowing resistance, ensuring high adhesion at temperatures below freezing point.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391310A_ABST
    Figure CN119391310A_ABST
Patent Text Reader

Abstract

The invention relates to a low-temperature-resistant and yellowing-resistant adhesive material and a preparation method and application thereof.The adhesive tape comprises a base material layer and an adhesive layer, the base material layer is prepared from modified ethylene acrylic acid copolymer, the adhesive layer is polyacrylate pressure-sensitive adhesive, and the base material layer is prepared from, by weight, 55-57 parts of EAA resin and 2.1-2.5 parts of fumed silica; 1.7 to 2.6 parts of silicone oil, 0.18 to 0.65 part of antioxidant and 0.2 to 0.3 part of phenyl salicylate; the polyacrylate pressure-sensitive adhesive is prepared from the following components in parts by weight: 80.4 to 82.6 parts of an acrylate polymer, 15.8 to 19 parts of a tackifier, 5.5 to 6.2 parts of a vulcanizing agent, 3.2 to 4.5 parts of a light stabilizer and 0.55 to 0.67 part of an auxiliary agent. Compared with the prior art, the adhesive tape disclosed by the invention has excellent stripping force, low-temperature adhesion performance and yellowing resistance, and can meet harsh application scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive materials, and in particular to a low temperature and yellowing resistant adhesive material and a preparation method and application thereof. Background Art

[0002] Adhesive tape is a common commodity in daily life. It is usually made of plastic film as the base material, and then the glue is evenly coated on the base material to make adhesive tape. Common base materials include BOPP, PE, PVC, and PET. For example, transparent tape made of transparent PET or BOPP film as the base material and modified acrylic pressure-sensitive adhesive coated on both sides has the characteristics of transparency and non-hygroscopicity, long-lasting adhesion, and water and steam resistance. At present, most adhesive tapes are only used for ordinary daily applications, but in the fields of leather industry, automobiles, membrane switches, electronic product repair, circuit boards, outdoor leisure repair, etc., high requirements are placed on the performance of adhesive tape materials. They must be able to maintain good adhesion performance in a wide temperature range such as ultra-high or ultra-low temperatures, especially they must have the transparent characteristics of UV resistance and long-term non-yellowing.

[0003] Chinese patent CN103242763A discloses a tape with a polyimide film as a substrate, in which a colloidal substance is glued to the polyimide film on a coating machine. The tape has great flexibility and elasticity when used, a long sticking time, and a good bonding effect on materials such as wood, leather, fabric, cardboard and plastic. Chinese patent CN106318255A discloses a preparation process for a transparent tape, in which a water-based pressure-sensitive adhesive is applied to a biaxially oriented polypropylene film substrate layer by a coating machine. Chinese patent CN103725231A discloses an adhesive material for tape, which is composed of a mixture of an acrylate prepolymer resin, a curing agent and a diluent solvent, and the adhesive material has good heat resistance and processing properties. However, existing tapes or adhesive materials cannot well balance adhesion and low temperature and yellowing resistance, and further research and development of adhesive tapes is still needed. Summary of the invention

[0004] The purpose of the present invention is to provide a low temperature resistant and yellowing resistant adhesive material and a preparation method and application thereof in order to solve the above problems.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A low temperature and yellowing resistant adhesive material, comprising a substrate layer and an adhesive layer, wherein:

[0007] The substrate layer is made of modified ethylene acrylic acid copolymer, and the adhesive layer is polyacrylate pressure-sensitive adhesive.

[0008] The substrate layer is composed of the following raw materials in parts by weight: 55-57 parts of EAA resin, 2.1-2.5 parts of fumed silica, 1.7-2.6 parts of silicone oil, 0.18-0.65 parts of antioxidant, and 0.2-0.3 parts of phenyl salicylate;

[0009] The polyacrylate pressure-sensitive adhesive comprises the following components in parts by weight: 80.4 to 82.6 parts of acrylate polymer, 15.8 to 19 parts of tackifier, 5.5 to 6.2 parts of vulcanizer, 3.2 to 4.5 parts of light stabilizer, and 0.55 to 0.67 parts of auxiliary agent.

[0010] As a preferred technical solution of the present invention, the substrate layer is composed of the following raw materials in parts by weight: 56 parts of EAA resin, 2.3 parts of fumed silica, 2.2 parts of silicone oil, 0.45 parts of antioxidant, and 0.25 parts of phenyl salicylate;

[0011] The polyacrylate pressure-sensitive adhesive comprises the following components in parts by weight: 81 parts of acrylate polymer, 17.8 parts of tackifier, 5.9 parts of vulcanizer, 3.8 parts of light stabilizer, and 0.59 parts of auxiliary agent.

[0012] As a preferred technical solution of the present invention, the EAA resin is selected from commercially available brands such as Primacor 1410, Primacor 1430 of Dow Chemical, DuPont Bynel EAA 2002, DuPont Nucrel EAA 31001, etc.

[0013] As a preferred technical solution of the present invention, the antioxidant is a hindered phenol antioxidant, preferably at least one of antioxidant 1908, antioxidant 1010, antioxidant 1070, and antioxidant 330.

[0014] As a preferred technical solution of the present invention, the substrate layer is prepared by the following preparation method:

[0015] Add EAA resin, fumed silica, silicone oil, antioxidant and phenyl salicylate into a mixer according to the proportion and stir evenly;

[0016] The mixed raw materials are put into a twin-screw extruder for granulation to obtain a masterbatch;

[0017] The obtained masterbatch is put into a tape casting machine to obtain a casting sheet;

[0018] The obtained cast sheet was biaxially stretched to obtain a film as a substrate layer.

[0019] In the EAA molecular structure, carboxyl groups are randomly distributed along the ethylene main chain and side chains, which are easy to combine with polar substances and can provide excellent adhesion. Due to the presence of carboxyl groups and the effect of hydrogen bonds, the crystallization of the polymer is suppressed, the linearity of the main chain is destroyed, and the transparency and toughness are improved. In addition to having excellent heat sealing, adhesion, transparency, and toughness, it also has good low-temperature performance and flexibility, and can meet the requirements for low-temperature use. The present invention further improves its yellowing resistance by compounding components such as fumed silica, antioxidants, and organic ultraviolet absorbers such as phenyl salicylate. Among them, fumed silica and phenyl salicylate have ultraviolet absorption and adsorption functions, which slow down the occurrence of light aging reactions, and adding antioxidants helps to slow down the aging rate.

[0020] As a preferred technical solution of the present invention, the acrylate polymer is prepared by the following method:

[0021] (a) Preparation of nanomaterial prepolymer: by weight, 4.5-5 parts of nano-organic silicon (e.g., dimethylcyclosiloxane), 3.8-4 parts of nano-titanium dioxide and 5-7 parts of silane coupling agent are added to a reaction kettle, stirred evenly at 45-50° C., 7-8 parts of hydroxyethyl acrylate and 5-6 parts of triethylamine are added, stirred and reacted for 2-3 hours to obtain a nanomaterial prepolymer;

[0022] (b) The nano material prepolymer participates in emulsion polymerization to prepare an acrylate polymer.

[0023] As a preferred technical solution of the present invention, the acrylic acid ester polymer is specifically prepared by the following method:

[0024] (1) adding 34-35 parts of water and 2.4-3 parts of sodium dodecylbenzene sulfonate by weight into a reaction kettle, stirring and heating to 78-85° C. to obtain a bottom liquid;

[0025] (2) adding 37-41 parts of water and 3.2-3.5 parts of sodium succinate sulfonate by weight into an emulsification tank and stirring, then adding 3.4-3.6 parts of hard monomer, 35-37 parts of soft monomer, 2.3-2.5 parts of nano material prepolymer, 1.4-1.5 parts of lauryl methacrylate, and 0.9-1 part of acrylic acid, and stirring uniformly to obtain a pre-emulsion;

[0026] (3) adding 4-5 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.35-0.37 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 10-15 minutes;

[0027] (4) Add the remaining pre-emulsion and 0.3-0.4 parts of ammonium persulfate to the reaction kettle simultaneously over 3-4 hours, and keep warm for 30-45 minutes after the addition is completed to obtain an acrylate polymer.

[0028] Acrylic pressure-sensitive adhesive has good bonding performance and good interfacial stress dispersion ability to the substrate, as well as heat resistance, no phase separation and migration phenomenon, but weather resistance needs to be provided. The present invention involves nano material prepolymer in emulsion polymerization, and after the silicone and nano titanium dioxide are treated with a silane coupling agent, they are fully combined with hydroxyethyl acrylate under the action of triethylamine to form a precursor prepolymer, and then participate in the subsequent polymerization process, avoiding the adverse effects of directly adding silicone and nano titanium dioxide on the performance of acrylic polymer. After adding silicone and nano titanium dioxide, it helps to improve the ultraviolet barrier and high temperature resistance, and significantly improves the aging resistance and yellowing resistance of the pressure-sensitive adhesive.

[0029] In a wide temperature range, adhesives are prone to various problems during use. On the one hand, under low temperature conditions, the molecular chain mobility of acrylic pressure-sensitive adhesives is weakened, the viscosity of the adhesive layer is reduced, and it is unable to form a sufficiently strong interaction force with the surface of the adherend, which reduces the peel strength. In addition, low temperature makes the adhesive layer brittle and reduces toughness, and the adhesive layer is prone to cracks and breaks, affecting the holding force. On the other hand, under high temperature conditions, the fluidity of the pressure-sensitive adhesive increases, and residual adhesive problems are prone to occur when the adhesive tape is removed. The present invention adds a relatively large amount of soft monomers to the acrylic pressure-sensitive adhesive formula, and at the same time adds long-chain hydrophobic methacrylate lauryl functional monomers and acrylic acid functional monomers, which helps to improve the low temperature resistance, moisture and heat resistance, etc. of acrylic acid.

[0030] As a preferred technical solution of the present invention, the hard monomer is selected from one or more of styrene, methyl methacrylate, methyl acrylate, and vinyl acetate, preferably styrene;

[0031] The soft monomer is selected from one or more of butyl acrylate, isooctyl acrylate, and ethyl acrylate, and butyl acrylate is preferred.

[0032] As a preferred technical solution of the present invention, the tackifier is selected from one or more of terpene resin, rosin, and C5 petroleum resin;

[0033] As a preferred technical solution of the present invention, the vulcanizing agent is nano zinc oxide.

[0034] As a preferred technical solution of the present invention, the light stabilizer is selected from organic light stabilizers, including ultraviolet absorbers (such as phenols, benzoic acids, dihydroxybenzophenones, etc.), photooxidative stabilizers (such as nitrophenols, nitrobenzoic acids, etc.), free radical scavengers (such as imines, thioethers, etc.), preferably, the light stabilizer is p-hydroxybenzoic acid or p-hydroxybenzamide.

[0035] As a preferred technical solution of the present invention, the auxiliary agent includes an antioxidant, and the antioxidant is antioxidant 1010.

[0036] As a preferred technical solution of the present invention, the adhesive layer is prepared by the following method: adding acrylate polymer, tackifier, vulcanizer, light stabilizer and additives into a rubber mixer and mixing them evenly, mixing them for 1 to 3 hours under vacuum conditions of -0.06 to -0.1 MPa and a temperature of 60 to 85°C, and naturally cooling to room temperature to obtain an adhesive.

[0037] As a preferred technical solution of the present invention, a method for preparing a low-temperature and yellowing-resistant adhesive material comprises the following steps: uniformly extruding the adhesive through an extruder and coating it on a substrate layer at the mouth of a molding die, wherein the thickness of the adhesive layer is 0.1 to 0.6 mm, and then rolling and automatically winding the adhesive layer after cooling by a roller, and then slitting and molding the adhesive material to obtain a product, wherein the thickness of the substrate layer is 0.05 to 0.5 mm.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention uses ethylene acrylic acid copolymer (EAA) as a substrate and polyacrylate pressure-sensitive adhesive as an adhesive. The molecular structure of EAA is distributed with carboxyl groups, which can be combined with polar substances and can be better combined with polyacrylate pressure-sensitive adhesives that are also distributed with a large number of carboxyl groups. The two have a large cohesive force, can maintain better low-temperature resistance, and provide excellent adhesion. In order to improve the yellowing resistance of the material, the ethylene acrylic acid copolymer and the polyacrylate pressure-sensitive adhesive are modified at the same time. The yellowing resistance of the ethylene acrylic acid copolymer is effectively improved by compounding fumed silica, antioxidants, and organic ultraviolet absorbers. In addition, the excellent performance of EAA itself has extremely high durability. The polyacrylate pressure-sensitive adhesive is optimized through the formulation process, and the ultraviolet barrier and high temperature resistance are improved by adding nanomaterial prepolymers, so that the aging resistance and yellowing resistance of the pressure-sensitive adhesive are significantly improved. At the same time, through the design of soft and hard monomers and functional monomers, excellent peeling force, low-temperature adhesion performance, moisture resistance, etc. are maintained, and high adhesion is still maintained at temperatures below freezing. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a physical picture of the sample prepared in the embodiment of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0042] In the following examples, raw materials or reagents not specifically described are all conventional components in the art and can be purchased through commercial channels.

[0043] [Preparation of substrate layer] Substrate samples A1 to A5

[0044] Prepare the raw materials according to the formula shown in Table 1.

[0045] Add all the raw materials into a mixer and stir and mix for about 30 minutes; put the mixed raw materials into a twin-screw extruder for granulation to obtain a masterbatch, the temperatures of the conveying section, melting section, mixing section, exhaust section and homogenizing section of the twin-screw extruder are 200°C, 220°C, 240°C, 240°C, 220°C, respectively, and the speed of the screw is 500r / min; put the obtained masterbatch into a casting machine to obtain a cast sheet, and biaxially stretch the obtained cast sheet to obtain a film with a thickness of 0.1mm.

[0046] Table 1 Raw material composition of substrate samples A1 to A5

[0047] EAA resin Fumed Silica Silicone oil Antioxidants Phenyl salicylate Substrate sample A1 56 2.3 2.2 0.45 0.25 Substrate sample A2 55 2.1 1.71 0.18 0.21 Substrate sample A3 56.8 2.46 2.6 0.65 0.29 Substrate sample A4 56 -- 2.2 0.45 0.25 Substrate sample A5 56 56 2.2 0.45 --

[0048] In sample A1, the EAA resin is Dow Chemical Primacor 1410; the fumed silica has a CAS number of 112945-52-5; the silicone oil has a CAS number of 63148-62-9; the antioxidant is antioxidant 1908, CAS number 23128-74-7; and the phenyl salicylate has a CAS number of 118-55-8.

[0049] In sample A2, the EAA resin is Primacor 1430 from Dow Chemical; the antioxidant is antioxidant 1010, CAS No. 3172-99-4, and the rest is the same as sample A1.

[0050] In sample A3, the EAA resin is DuPont Bynel EAA2002; the antioxidant is antioxidant 1070, CAS No. 3172-99-4, and the rest is the same as sample A1

[0051] Sample A4 and Sample A5 are the same as Sample A1 except for the components not added.

[0052]

Adhesive layer preparation

[0053] Prepare the raw materials according to the formula shown in Table 2.

[0054] Add acrylate polymer, tackifier, vulcanizer, light stabilizer and additives into a rubber mixer and mix evenly. Mix for 2 hours at 75°C under a vacuum condition of about -0.08 and then cool to room temperature to obtain an adhesive.

[0055] Table 2 Raw material composition of adhesive samples B1 to B5

[0056] Acrylate polymer Tackifier Vulcanizing agent Light Stabilizer Antioxidants Adhesive sample B1 81 17.8 5.9 3.8 0.59 Adhesive sample B2 80.4 15.8 5.5 3.2 0.55 Adhesive sample B3 82.6 19 6.2 4.5 0.67 Adhesive sample B4 81 17.8 5.9 3.8 0.59 Adhesive sample B5 81 17.8 5.9 3.8 0.59 Adhesive sample B6 81 17.8 5.9 3.8 0.59

[0057] In adhesive samples B1 to B6, the tackifier is terpene resin, CAS number 9003-74-1; the vulcanizer is nano zinc oxide, CAS number 1314-13-2; the light stabilizer is p-hydroxybenzoic acid, CAS number 99-96-7; and the antioxidant is antioxidant 1010, CAS number 3172-99-4.

[0058] In the adhesive samples B1 to B6, the acrylate polymers are acrylate polymers C1 to C6, respectively, which are prepared by the following method.

[0059] Acrylate polymer C1

[0060] It is prepared specifically by the following method:

[0061] (1) Preparation of nanomaterial prepolymer: Add 4.7 parts of dimethylcyclosiloxane, 3.9 parts of nano titanium dioxide (13463-67-7) and 6 parts of silane coupling agent A151 to a reaction kettle by weight, stir evenly at 50° C., add 7.5 parts of hydroxyethyl acrylate and 5.5 parts of triethylamine, stir and react for 3 hours to obtain a nanomaterial prepolymer for later use;

[0062] (2) 34.5 parts of water and 2.7 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) were added into a reaction kettle, stirred and heated to 80° C. to obtain a bottom liquid;

[0063] (3) Add 39 parts of water and 3.4 parts of sodium succinate sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.5 parts of styrene, 36 parts of butyl acrylate, 2.4 parts of nanomaterial prepolymer, 1.45 parts of lauryl methacrylate (BASFLMA 1214F), and 0.95 parts of acrylic acid, and stir to obtain a pre-emulsion;

[0064] (4) adding 4 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.36 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 13 minutes;

[0065] (5) The remaining pre-emulsion and 0.35 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 3.5 hours. After the addition was completed, the mixture was kept warm for 30 minutes to obtain an acrylate polymer.

[0066] Acrylate polymer C2

[0067] It is prepared specifically by the following method:

[0068] (1) Preparation of nanomaterial prepolymer: Add 4.5 parts of dimethylcyclosiloxane, 3.8 parts of nano titanium dioxide (13463-67-7) and 5 parts of silane coupling agent A151 to a reaction kettle by weight, stir evenly at 45° C., add 7 parts of hydroxyethyl acrylate and 5 parts of triethylamine, stir and react for 2 hours to obtain a nanomaterial prepolymer for later use;

[0069] (2) Add 34 parts of water and 2.4 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) by weight into a reaction kettle, stir and heat to 80° C. to obtain a bottom liquid;

[0070] (3) Add 37 parts of water and 3.2 parts of sodium succinate sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.4 parts of styrene, 35 parts of butyl acrylate, 2.3 parts of nanomaterial prepolymer, 1.4 parts of lauryl methacrylate (BASFLMA 1214F), and 0.9 parts of acrylic acid, and stir to obtain a pre-emulsion;

[0071] (4) adding 4 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.35 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 10 minutes;

[0072] (5) The remaining pre-emulsion and 0.3 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 3 hours. After the addition was completed, the mixture was kept warm for 40 minutes to obtain an acrylate polymer.

[0073] Acrylate polymer C3

[0074] It is prepared specifically by the following method:

[0075] (1) Preparation of nanomaterial prepolymer: Add 5 parts of dimethylcyclosiloxane, 4 parts of nano titanium dioxide (13463-67-7) and 7 parts of silane coupling agent A151 to a reaction kettle by weight, stir evenly at 50° C., add 8 parts of hydroxyethyl acrylate and 6 parts of triethylamine, stir and react for 3 hours to obtain a nanomaterial prepolymer for later use;

[0076] (2) Add 35 parts of water and 3 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) by weight into a reaction kettle, stir and heat to 80° C. to obtain a bottom liquid;

[0077] (3) Add 41 parts of water and 3.5 parts of sodium succinate sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.6 parts of styrene, 37 parts of butyl acrylate, 2.5 parts of nanomaterial prepolymer, 1.5 parts of lauryl methacrylate (BASFLMA 1214F), and 1 part of acrylic acid, and stir to obtain a pre-emulsion;

[0078] (4) adding 5 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.37 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 15 minutes;

[0079] (5) The remaining pre-emulsion and 0.4 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 4 hours. After the addition was completed, the mixture was kept warm for 40 minutes to obtain an acrylate polymer.

[0080] Acrylate polymer C4

[0081] Compared with the acrylate polymer C1, step (1) is omitted, that is, no nanomaterial prepolymer is added.

[0082] It is prepared specifically by the following method:

[0083] (1) Add 34.5 parts of water and 2.7 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) by weight into a reaction kettle, stir and heat to 80° C. to obtain a bottom liquid;

[0084] (2) Add 39 parts of water and 3.4 parts of sodium succinate octyl sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.5 parts of styrene, 36 parts of butyl acrylate, 1.45 parts of lauryl methacrylate (BASF LMA 1214F), and 0.95 parts of acrylic acid, and stir to obtain a pre-emulsion;

[0085] (3) adding 4 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.36 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 13 minutes;

[0086] (4) The remaining pre-emulsion and 0.35 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 3.5 hours. After the addition was completed, the mixture was kept warm for 30 minutes to obtain an acrylate polymer.

[0087] Acrylate polymer C5

[0088] Compared with the acrylate polymer C1, step (1) is omitted, and the same equivalent amount of dimethylcyclosiloxane and nano-titanium dioxide are directly added during the polymerization process.

[0089] It is prepared specifically by the following method:

[0090] (1) Add 34.5 parts of water and 2.7 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) by weight into a reaction kettle, stir and heat to 80° C. to obtain a bottom liquid;

[0091] (2) Add 39 parts of water and 3.4 parts of sodium succinate octyl sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.5 parts of styrene, 36 parts of butyl acrylate, 0.4 parts of dimethylcyclosiloxane, 0.34 parts of nano titanium dioxide, 1.45 parts of lauryl methacrylate (BASF LMA 1214F), and 0.95 parts of acrylic acid, and stir to obtain a pre-emulsion;

[0092] (3) adding 4 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.36 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 13 minutes;

[0093] (4) The remaining pre-emulsion and 0.35 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 3.5 hours. After the addition was completed, the mixture was kept warm for 30 minutes to obtain an acrylate polymer.

[0094] Acrylate polymer C6

[0095] Compared with the acrylate polymer C1, the functional monomer lauryl methacrylate is not added in step (3).

[0096] Prepared by the following method:

[0097] (1) Preparation of nanomaterial prepolymer: Add 4.7 parts of dimethylcyclosiloxane, 3.9 parts of nano titanium dioxide (13463-67-7) and 6 parts of silane coupling agent A151 to a reaction kettle by weight, stir evenly at 50° C., add 7.5 parts of hydroxyethyl acrylate and 5.5 parts of triethylamine, stir and react for 3 hours to obtain a nanomaterial prepolymer for later use;

[0098] (2) 34.5 parts of water and 2.7 parts of sodium dodecylbenzene sulfonate (CAS No. 25155-30-0) were added into a reaction kettle, stirred and heated to 80° C. to obtain a bottom liquid;

[0099] (3) Add 39 parts of water and 3.4 parts of sodium succinate sulfonate (CAS No. 577-11-7) by weight into an emulsification tank and stir, then add 3.5 parts of styrene, 36 parts of butyl acrylate, 2.4 parts of nano material prepolymer, and 0.95 parts of acrylic acid, and stir evenly to prepare a pre-emulsion;

[0100] (4) adding 4 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.36 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 13 minutes;

[0101] (5) The remaining pre-emulsion and 0.35 parts of ammonium persulfate were simultaneously added dropwise to the reaction kettle within 3.5 hours. After the addition was completed, the mixture was kept warm for 30 minutes to obtain an acrylate polymer.

[0102]

Yellowing resistance test

[0103] The substrate samples A1-A5 and adhesive samples B1-B6 were subjected to aging and yellowing resistance tests in an accelerated aging and yellowing resistance test chamber. The specific test results are shown in Table 3.

[0104] The substrate samples were compared with the color difference of the substrate samples before and after the test using a colorimeter according to the standard ISO 4892-3:2016 "Plastics - Laboratory light source exposure test methods - Part 3: Fluorescent ultraviolet lamp". The substrate samples were divided into four levels according to the degree of yellowing: severe yellowing, yellowing, slight yellowing, and no yellowing.

[0105] The adhesive samples are measured for discoloration (yellowing) performance of adhesives in accordance with the standard GB / T 39294-2020. The adhesive is evenly coated on a clean and dry standard glass sheet, placed in a test chamber, and heated continuously at 90°C for 72 hours. The color change is observed using a colorimeter. The adhesive is divided into four levels according to the degree of yellowing: severe yellowing, yellowing, slight yellowing, and no yellowing.

[0106] Table 3 Yellowing resistance test results of samples A1~A5 and B1~B6

[0107]

[0108] [Adhesive tape preparation] Adhesive tape samples E1 to E10

[0109] Samples A1 to A3 and samples B1 to B3 and B6 that do not yellow are selected to prepare adhesive tape products. The adhesive tape samples are prepared according to the raw material composition shown in Table 4.

[0110] The specific preparation method is: the adhesive is uniformly extruded through an extruder and coated on the substrate layer at the mouth of the molding die, the thickness of the adhesive layer is about 0.25mm, and then automatically rolled up after rolling and cooling by a roller machine, and cut into pieces to obtain a tape product with a serrated edge (such as Figure 1 As shown), the substrate thickness is 0.1 mm.

[0111] Table 4 Raw material composition of adhesive tape samples E1 to E10

[0112]

[0113]

[0114] In Table 4, the substrate of sample E9 is BOPP film purchased from Guangdong Changtuniu Film Technology Co., Ltd.;

[0115] The substrate of sample E10 is PE film purchased from Guangdong Changtuniu Film Technology Co., Ltd., and the adhesive Y is Baolijia BLJ-532.

[0116]

Adhesive tape sample performance test

[0117] The performance of samples E1 to E10 were tested. Three groups of experiments were conducted and the average value of the three groups was taken as the test result. The test results are detailed in Table 5.

[0118] Peel strength (N / 25mm): Tested in accordance with standard GB / T 2792-2014 "Test method for peel strength of adhesive tapes". For low-temperature peel strength test, place the test sample at -10℃ for more than 16 hours before testing.

[0119] Adhesion (h): Tested in accordance with GB / T4851-2014 "Test Method for Adhesion of Adhesive Tapes", expressed as drop time. For low-temperature adhesion test, place the test sample at -10℃ for more than 16 hours before testing.

[0120] Residual glue evaluation: Attach the test sample to a clean test steel plate and place it in a constant temperature and humidity chamber at 60°C and 90% humidity. Take it out after 48 hours and place it under standard conditions for 2 hours. Remove the adhesive tape and observe whether there is residual glue and contamination of the steel plate.

[0121] Table 5 Performance test results of adhesive tape samples E1 to E10

[0122] Peel force -10℃ low temperature peel strength Holding force / h -10℃ low temperature holding force / h Residual glue Sample E1 15.6 12.4 ≥168 ≥72 No residual glue, no stain Sample E2 14.7 12.5 ≥168 ≥72 No residual glue, no stain Sample E3 15.1 11.9 ≥168 ≥72 No residual glue, no stain Sample E4 14.2 11.3 ≥168 ≥72 No residual glue, no stain Sample E5 13.2 10.9 ≥168 ≥72 Slight adhesive residue Sample E6 13.9 11.2 ≥168 ≥72 Slight adhesive residue Sample E7 14.2 8.3 ≥168 ≤48 Residual glue stain Sample E8 14.5 7.0 ≥168 ≤48 Residual glue stain Sample E9 13.3 9.7 ≥168 ≤72 Severe adhesive contamination Sample E10 10.6 5.3 ≥168 ≤24 Severe adhesive contamination

[0123] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A low temperature and yellowing resistant adhesive material, comprising a substrate layer and an adhesive layer, characterized in that: The substrate layer is made of modified ethylene acrylic acid copolymer, and the adhesive layer is polyacrylate pressure-sensitive adhesive. The substrate layer is composed of the following raw materials in parts by weight: 55-57 parts of EAA resin, 2.1-2.5 parts of fumed silica, 1.7-2.6 parts of silicone oil, 0.18-0.65 parts of antioxidant, and 0.2-0.3 parts of phenyl salicylate; The polyacrylate pressure-sensitive adhesive comprises the following components in parts by weight: 80.4 to 82.6 parts of acrylate polymer, 15.8 to 19 parts of tackifier, 5.5 to 6.2 parts of vulcanizer, 3.2 to 4.5 parts of light stabilizer, and 0.55 to 0.67 parts of auxiliary agent.

2. The low temperature and yellowing resistant adhesive material according to claim 1, characterized in that: The EAA resin is selected from the commercially available brands of Dow Chemical's Primacor 1410, Primacor 1430, DuPont Bynel EAA 2002, and DuPont Nucrel EAA 31001; And / or, the antioxidant is a hindered phenol antioxidant, selected from at least one of antioxidant 1908, antioxidant 1010, antioxidant 1070, and antioxidant 330.

3. The low temperature and yellowing resistant adhesive material according to claim 1, characterized in that: The substrate layer is prepared by the following preparation method: Add EAA resin, fumed silica, silicone oil, antioxidant and phenyl salicylate into a mixer according to the proportion and stir evenly; The mixed raw materials are put into a twin-screw extruder for granulation to obtain a masterbatch; The obtained masterbatch is put into a tape casting machine to obtain a casting sheet; The obtained cast sheet is biaxially stretched to obtain a film.

4. The low temperature and yellowing resistant adhesive material according to claim 1, characterized in that: The acrylic acid ester polymer is prepared by the following method: (a) Preparation of nanomaterial prepolymer: Add 4.5-5 parts of nano-organic silicon, 3.8-4 parts of nano-titanium dioxide and 5-7 parts of silane coupling agent to a reaction kettle by weight, stir evenly at 45-50° C., add 7-8 parts of hydroxyethyl acrylate and 5-6 parts of triethylamine, stir and react for 2-3 hours to obtain a nanomaterial prepolymer; (b) The nano material prepolymer participates in emulsion polymerization to prepare an acrylate polymer.

5. The low temperature and yellowing resistant adhesive material according to claim 4, characterized in that: The acrylic acid ester polymer is specifically prepared by the following method: (1) adding 34-35 parts of water and 2.4-3 parts of sodium dodecylbenzene sulfonate by weight into a reaction kettle, stirring and heating to 78-85° C. to obtain a bottom liquid; (2) adding 37-41 parts of water and 3.2-3.5 parts of sodium succinate sulfonate by weight into an emulsification tank and stirring, then adding 3.4-3.6 parts of hard monomer, 35-37 parts of soft monomer, 2.3-2.5 parts of nano material prepolymer, 1.4-1.5 parts of lauryl methacrylate, and 0.9-1 part of acrylic acid, and stirring uniformly to obtain a pre-emulsion; (3) adding 4-5 wt% of the total amount of the pre-emulsion into a reaction kettle, adding 0.35-0.37 parts of sodium octyl succinate sulfonate, and carrying out polymerization reaction for 10-15 minutes; (4) Add the remaining pre-emulsion and 0.3-0.4 parts of ammonium persulfate to the reaction kettle simultaneously over 3-4 hours, and keep warm for 30-45 minutes after the addition is completed to obtain an acrylate polymer.

6. The low temperature and yellowing resistant adhesive material according to claim 5, characterized in that: The hard monomer is selected from one or more of styrene, methyl methacrylate, methyl acrylate, and vinyl acetate, preferably styrene; And / or, the soft monomer is selected from one or more of butyl acrylate, isooctyl acrylate, and ethyl acrylate, preferably butyl acrylate.

7. The low temperature and yellowing resistant adhesive material according to claim 5, characterized in that: The tackifier is selected from one or more of terpene resin, rosin, and C5 petroleum resin; And / or, the vulcanizing agent is nano zinc oxide; and / or, the light stabilizer is selected from organic light stabilizers, including ultraviolet absorbers, light oxidation stabilizers, and free radical scavengers; And / or, the auxiliary agent includes an antioxidant.

8. The low temperature and yellowing resistant adhesive material according to claim 1, characterized in that: The adhesive layer is prepared by the following method: adding acrylate polymer, tackifier, vulcanizer, light stabilizer and additives into a rubber mixer and mixing them evenly, mixing them for 1 to 3 hours under a vacuum condition of -0.06 to -0.1 MPa and a temperature of 60 to 85° C., and naturally cooling to room temperature to obtain an adhesive.

9. The method for preparing a low temperature and yellowing resistant adhesive material according to claim 1, characterized in that: The following steps are involved: The adhesive is uniformly extruded through an extruder and coated onto the substrate layer at the mouth of a molding die, and then automatically rolled up after being pressed and cooled by a roller, and then cut and formed to obtain a product, wherein the thickness of the substrate layer is 0.05 to 0.5 mm, and the thickness of the adhesive layer is 0.1 to 0.6 mm.

10. The use of a low temperature and yellowing resistant adhesive material as claimed in claim 1, characterized in that: The adhesive tape is used in leather industry, automobiles, plastic inflatables, outdoor repair, plastic repair.

Citation Information

Patent Citations

  • Manufacturing method of adhesive tape taking polyimide film as base material

    CN103242763A

  • Adhesive material for adhesive tapes and preparation method thereof

    CN103725231A

  • Preparation technology of transparent tape

    CN106318255A